The Banda Infanta. On Gender’s Unspeakable Truth - Eggen, Wiel (Studia Gdańskie, 2021)
On gender’s unspeakable truth. The genders’ social role is arguably of prime interest to a young woman entering adult life. Calling her the Infanta, after Velasquez’ famous painting of the Spanish Princess, this article looks at the Central-African Republic, the Banda society, to analyze what is implied for a girl at her initiation ritual, given the striking use of the their term for ‘mother’ (əyi), not just to indicate the genetrix and any female, fertile and imposing creature, but also to designate owners of property, male or female, and masters or incumbents of a social position. With the mother-related social domain offering solace for patrilineal demands, and notably for the menace of witchcraft, it appears that this remarkable term presents a basic value that transcends all gender differentiations, and the rivalries they involve.